2016
DOI: 10.1111/opo.12340
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation stimulus and response determinations with autorefractors

Abstract: Accurate equations for accommodation stimulus and accommodation response for a range of accommodation stimuli in different setups have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 19 publications
(31 reference statements)
0
27
0
Order By: Relevance
“…These measurements were captured using a COAS-HD wavefront sensor (produced by the former company, Wavefront Sciences Inc., later acquired by Lumetrics, www.lumetrics.com), which is based on the Hartmann-Shack principle and has been well-validated. 26,27 An eighth order Zernike polynomial was fit across a 2.3 mm pupil for each participant at each accommodation demand, from which the refractive power vectors, M, J 180 , and J 45 , were determined from the wavefront slope using the methods of Iskander et al 28 Atchison and Varnas 29 suggested that accommodation measurements obtained using autorefractors depend on several factors, including the method used to stimulate accommodation, and discrepancies between subjective and objective refraction measurements. Since the accommodation demands presented via the Badal optometer were based on the non-cycloplegic subjective refraction and the accommodation response (and errors) were determined using measurements from the COAS-HD, the equations presented by Atchison and Varnas 29 were used to determine the "adjusted" accommodation errors, where a negative and positive value indicates a lead and lag of accommodation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These measurements were captured using a COAS-HD wavefront sensor (produced by the former company, Wavefront Sciences Inc., later acquired by Lumetrics, www.lumetrics.com), which is based on the Hartmann-Shack principle and has been well-validated. 26,27 An eighth order Zernike polynomial was fit across a 2.3 mm pupil for each participant at each accommodation demand, from which the refractive power vectors, M, J 180 , and J 45 , were determined from the wavefront slope using the methods of Iskander et al 28 Atchison and Varnas 29 suggested that accommodation measurements obtained using autorefractors depend on several factors, including the method used to stimulate accommodation, and discrepancies between subjective and objective refraction measurements. Since the accommodation demands presented via the Badal optometer were based on the non-cycloplegic subjective refraction and the accommodation response (and errors) were determined using measurements from the COAS-HD, the equations presented by Atchison and Varnas 29 were used to determine the "adjusted" accommodation errors, where a negative and positive value indicates a lead and lag of accommodation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is also important to understand an important limitation of the technique: the use of the red stimulus could have caused greater accommodative stimulus and, consequently, higher accommodative responses. Due to the chromatic aberrations of the human eye, there is a higher accommodation when the subject reads with red light [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The entire testing was conducted through the subject’s best distance refraction. This study used the formulas suggested by Atchison and Varnas (2017) to calculate the accommodative stimulus, accommodative response, and accommodative lag/lead for each participant at the three accommodative demands [ 37 ]. The calculation steps of the three formulas are where AS represents accommodative stimulus; L , object vergence; d , vertex distance; and SR , spectacle refraction.…”
Section: Methodsmentioning
confidence: 99%